FEATURES OF THE CYTOKINE TYPE OF REGULATION OF THE IMMUNE RESPONSE IN PATIENTS WITH ERYSIPELAS - Vasilevska, L.A.; Shapoval, S.D.; Vorontsova, L.L. (World of Medicine and Biology, 2022)
The study of the problems of changes in the cytokine status in erysipelas shows the absence in the studies of other authors of a precise distribution into the forms and types of the course of the disease. This makes it impossible to determine the cytokine type of immune response for the appointment of an individual pathogenetically substantiated treatment. We analyzed the state of the granulocytic link of the phagocytic system, cytokine status, types of immune response, taking into account the form (erythematous, bullous, phlegmonous-necrotic) and the type of course of erysipelas (primary and recurrent, which are complicated by sepsis). Incomplete phagocytosis against the background of a deficit in the functional and metabolic reserve of neutrophils is observed in groups with sepsis and in the recurrent course of the phlegmonous-necrotic form. Changes in immune response regulation from Th2-type (erythematous form) to Th1-type (sepsis) were revealed in primary erysipelas and all recurrent erysipelas. Bullous and phlegmonous-necrotic forms of primary erysipelas are characterized by an immune response of the Th1/Th2 type (with the predominance of the Th1 type). The revealed changes indicate a sharply increasing bacterial load and the severity of the disease. Determining the types of the regulation characteristic of patients with various forms and courses of the disease indicates the need for an individual approach to treatment and the mandatory prescription of drugs with an immunomodulatory effect.
Keywords: erysipelas; microbial landscape; cytokines; phagocytosis; functional and metabolic status of neutrophils